IMAGOLOGY AND TRANSLATION – ON THE EXAMPLE OF POLISH TRANSLATION OF CZECH LITERATURE - Németh Vítová, Lenka (Porównania, 2019)
The author, asking about relations between imagology and translation, is looking for an answer on the example of Polish translations of Czech literature (Hašek, Hrabal, Havel). These relations should be found in the process of translation (selection of a specific work and translator, publication and promotion, other conditioning factors, etc.), as well as in the translated text (its textual, editorial and iconographic aspects), and also in the reception process of the translated text (reviews and studies, adaptations, „canonization” and its role in the educational process, etc.). Close relation between translation and imagology, resulting largely from the „invisibility of the translator” adopted in our cultures (Venuti 1995), should therefore be one of the areas of posthuman research.